Relationship between head posture and lumbar curve in a sitting position: a biomechanical study - Rozilene Maria Cota Aroeira; Renata Maria Moreira Moraes Furlan; Antônio Eustáquio de Melo Pertence; Estevam Barbosa de Las Casas; Marcelo Greco
Abstract Introduction: The sitting position routinely used for a wide variety of tasks increases the potential of developing forward head posture, which can seriously compromise the health of different systems in the human body. Objective: A static equilibrium analysis was conducted, comparing the position of the head with the lumbar curve in three different sitting positions. Methods: The approximate force and flexion moment of the head extensor muscles in static equilibrium was calculated in each of the following positions: (A) without a backrest; (B) using a backrest with a 100° tilt angle; (C) using a 100° tilted backrest associated with a cylindrical lumbar support cushion at the level of the L3 vertebra. Results: The C7-tragus angles were 43°, 50° and 52°; Frankfort horizontal plane (FH) angles were 5°, 9° and 9°; force of the head extensor muscles was 53.0N, 59.7N and 43.5N and flexion moments were 2.60Nm, 2.05Nm and 1.78Nm, in positions A, B and C, respectively. Conclusion: The results revealed that the sitting position using a 100° tilted backrest and lumbar support with the smallest L3-tragus horizontal distance required less effort by the head and neck extensor muscles to retain the head in equilibrium. This study demonstrated the need to preserve the physiology of the lumbar spine, characterized by the position of the L3 vertebra, in order to ensure good head position.